Baalbek, Libanon: Forschungen im Steinbruch und Aufarbeitung der Arbeiten 2001 bis 2012 - van Ess, Margarete (e-Forschungsberichte des DAI, 2023)
On behalf of the German Archaeological Institute and in close cooperation with local institutions Lebanese specialists continued the excavation in the famous quarry south of Baalbek. The northern, western and southern areas next to the well-known “Hajjar al-Hibla” megalith were unearthed and further traces of Roman quarry technics detected. In the western part of the quarry a number of grave chambers came to light cut into the quarry in secondary use.